2008
DOI: 10.3923/pjbs.2008.2073.2082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Environmental Parameters on Hydrogen Production Using C. acetobutylicum

Abstract: The aim of this study was to investigate the influence of some environmental factors on bacterial metabolism. Fermentative hydrogen production by C. acetobutylicum, using glucose as the substrate. The effect of initial pH (4-8), inoculum size (1-20% (v/v)) and glucose concentration (1-30 g L(-1)) on hydrogen production were studied. The optimum cultivation temperature for hydrogen production was at 30 degrees C. The results show that substrate concentration and inoculum size resulted in hydrogen yield (Y(P/S))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Sodium is required by microorganisms in different quantities, since it regulates cell osmosis. At high concentrations, this element may inhibit cell growth [1,19]. Finally, iron influences cell growth and takes participates in the synthesis of several proteins, in electron transport, and in the constitution of cytochromes, in addition to hydrogenases functioning [1,19].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Sodium is required by microorganisms in different quantities, since it regulates cell osmosis. At high concentrations, this element may inhibit cell growth [1,19]. Finally, iron influences cell growth and takes participates in the synthesis of several proteins, in electron transport, and in the constitution of cytochromes, in addition to hydrogenases functioning [1,19].…”
Section: Resultsmentioning
confidence: 98%
“…It is an essential element for the synthesis of proteins, amino acids and other cellular compounds [1,19].For the stability of the ribosome and synthesis of many enzymes, magnesium is essential [1,19]. Calcium helps in the stabilization of cell walls and in the thermostability of endospores [1,19]. Sodium is required by microorganisms in different quantities, since it regulates cell osmosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at higher concentrations, iron and nickel may inhibit the process [11]. Alshiyab et al (2008) investigated the impact of Fe 2þ ions concentration (0e1000 mg/L) on the batch hydrogen fermentation from glucose using Clostridium acetobutylicum, and reported that the hydrogen yield was enhanced from 391 to 408 mL/g-VS at Fe 2þ ions concentration of 25 mg/L, while the higher concentrations of Fe 2þ ions negatively affected the yield [13]. Wang and Wan (2008) investigated the impact of Ni 2þ ions on the batch hydrogen fermentation using mixed culture and reported that Ni 2þ ions concentrations below 0.1 mg/L could increase the hydrogen yield.…”
Section: Introductionmentioning
confidence: 99%